Building with Water: new Standards of Sustainable Architecture - Cesare Sposito (Agathón)
Within an increasingly consolidated architectural practice aiming at environmental sustainability and energy self-sufficiency, the article reports international research and experiments carried out on water-architecture. Furthermore, it highlights how, starting from the excellent capacity of the fluid to heat and cool its surrounding space, we can think to water as a material component of architecture.